Performance Evaluation of Participatory Development Programs in the Context of Inclusive Governance: A Study in Rangkasbitung Subdistrict, Lebak Regency, Banten - Habib Cahyono; Bimby Hidayat; Mukhamad Zulianto; Mulyadi Mulyadi (Universitas Teuku Umar, 2026)
Participatory development programs are an important instrument in realizing inclusive governance in Indonesia. This study aims to evaluate the performance of participatory development programs in Rangkasbitung Subdistrict, Lebak Regency, Banten, with a focus on community participation, transparency, accountability, and development impact. Using a qualitative approach with a case study method, this study analyzes the implementation of participatory development programs. The results show that although there has been an improvement in the performance of development programs in the context of inclusive governance, challenges remain in terms of the quality of participation, representation of marginalized groups, and program sustainability. This study provides recommendations for strengthening the capacity of local institutions, improving community literacy, and developing more effective monitoring and evaluation mechanisms